DISTRIBUTION AND RESOURCES OF YESSO SCALLOP MIZUHOPECTEN YESSOENSIS IN THE SAKHALINKURIL REGION ON RESULTS OF THEIR EXPLOITATION FROM 2000 TO 2011 - D. A. Galanin; N. Yu. Prokhorova; V. A. Sergeenko; Yu. S. Chernyshova; T. A. Shpakova (Известия ТИНРО, 2019)
Results of commercial exploitation of the yesso scallop resources in the Sakhalin-Kuril region in 2000–2011 are analyzed, taking into account the data of diving surveys at the depth of 2–30 m (on average 5 stations with sampling from 50 m2 per transect) in the 2009–2012. The results are compared with published and archived data for unexploited period. Range of the scallop spatial distribution did not changed. Size of the scallop increased, but its abundance and biomass decreased, in general, in particular in the Aniva Bay and on the shoal at southern Kuril Islands, though the scallop became more abundant in the Aleksandrovsky Bay and Patience Bay. The stocks reducing in the Aniva Bay was possibly caused by lack of feeding.